Productivity and Quality of Fodder Oats (Avena sativa L.) as influenced by Sowing Time, Cutting Schedules and Nitrogen Levels - Kadam, S S; Solanki, N S; Arif, Mohd.; Dashora, L. N.; Mundra, S. L.; Upadhyay, B. (Indian Journal of Animal Nutrition, 2019)
A field experiment was conducted at Agronomy Farm, Rajasthan College of Agriculture, Udaipur, (Rajasthan) during rabi seasons of 2016-17 and 2017-18 to study the effect of sowing time (25th October and 25th November), cutting schedules (Cut at 50 DAS, Cut at 60 DAS and Cut at 70 DAS) and nitrogen levels (80, 100 and 120 kg ha-1) on productivity and quality of fodder oats. Â It was revealed that early sown crop on 25th October recorded significantly higher green and dry fodder yield as well as green and dry fodder production efficiency and quality parameters viz. ether extract, ash content. Among different cutting schedules, cut at 70 DAS recorded significantly higher green and dry fodder yield of oats over rest of cutting schedules. However, cut at 50 DAS proved significantly better in terms of green and dry fodder production efficiency as well as quality parameters viz. crude protein, ether extract, and ash content. Application of 120kg N ha-1 gave significantly higher green, dry fodder yield and green, dry fodder production efficiency and quality parameters viz. crude protein, ether extract and ash content.